Temporomandibular disorders in adolescents with parafunctional habits - Lidia Beatriz Caraballo Villalón; Melba Alina Borges Toirac; Prudencia Villalón Artires; Maritania Balleuxs Pereira (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Temporomandibular disorders in adolescents can be caused by parafunctional habits that probably lead to different manifestations in the stomatognathic system՚s components. Objective: To characterize the adolescents with temporomandibular disorders and parafunctional habits according to epidemiologic and clinical variables. Methods: An observational, descriptive and cross-sectional study of 74 adolescents (15-18 years) from Antonio Alomá Serrano Senior High School, belonging to the health area of José Martí University Polyclinic in Santiago de Cuba, was carried out from November, 2021 to March, 2022. Results: It was found that 88.1% of the members in the series presented light alterations, 11.9% presented moderate changes and 20.3% didn't have any changes. Of the 59 patients with temporomandibular disorders, 74.6% were women, with prevalence of the light alterations (76.9%). The habit referred with more frequency was nail biting (50.8%), followed by cheilophagia (47.5%). Of the adolescents that presented bruxism, 71.4% showed a moderate dysfunction; however, in those with light dysfunction the practice of nail biting prevailed (53.8%). Conclusions: Most of the adolescents with more than one parafunctional habit presented temporomandibular disorders.